2022
DOI: 10.5114/ada.2022.118921
|View full text |Cite
|
Sign up to set email alerts
|

The use of isotretinoin in acne therapy in early childhood and its effect on the occurrence of acne symptoms later in life. Eight-year follow-up

Abstract: Introduction: Acne vulgaris is a chronic inflammatory skin disease of the pilosebaceous follicles that affects patients of all ages. Aim: Use of isotretinoin in the early stages of the disease to prevent subsequent lesions of acne, including prolonged treatment and acne scars at a later age. Material and methods: A retrospective, comparative study was carried between January 2010 and November 2018. The study population consisted of 90 children aged 9-18 years with acne. During treatment by isotretinoin the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…However, among those who did stop using isotretinoin, 15.9% ceased usage less than two months ago, while 10.3% stopped more than two months ago. These findings align with the study, which reported similar proportions of participants who discontinued isotretinoin usage within different timeframes [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, among those who did stop using isotretinoin, 15.9% ceased usage less than two months ago, while 10.3% stopped more than two months ago. These findings align with the study, which reported similar proportions of participants who discontinued isotretinoin usage within different timeframes [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 91%
“… 13 , 14 , 30 It might be because that treatment with ISO could result in a decrease in skin hydration. 42 In the study proved by Brzezinski et al, 15 concluding 90 teenagers with acne treated with ISO, the incidence of dry lips was 100%. Chapped lips were also the adverse reaction.…”
Section: Resultsmentioning
confidence: 93%
“… 13 Vallerand et al 14 collected data from 11 trials meeting eligibility for review (total 760 patients randomized) and found that the rate of adverse events was twice as high in the ISO group compared to the control group across all trials. In a 2022 study by Brzezinski et al 15 of 90 adolescent participants treated with ISO for acne, 11 different adverse effects were noted during ISO treatment. Next, we begin to tease out the physical side effects of ISO treatment with the three prominent adverse effects mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…The study divided patients into three groups (A, B, C) based on age that were followed up for one to eight years. The results showed that 73.33% of children in Group C experienced acne scars and post-acne hyperpigmentation [ 22 ]. Elshafie et al [ 21 ] reported that among 103 Egyptian dermatologists, 92.8% of them sometimes prescribed isotretinoin alone for moderate to severe nodulo-cystic acne, 4.5% rarely prescribed it (only for a case with primary comedone), and 2.7% always prescribed the drug for all acne types.…”
Section: Discussionmentioning
confidence: 99%